Awareness and Attitude Toward Artificial Intelligence Among Medical Students and Pathology Trainees: Survey Study - Anwar Rjoop; Mohammad Al-Qudah; Raja Alkhasawneh; Nesreen Bataineh; Maram Abdaljaleel; Moayad A Rjoub; Mustafa Alkhateeb; Mohammad Abdelraheem; Salem Al-Omari; Omar Bani-Mari; Anas Alkabalan; Saoud Altulaih; et al. (JMIR Medical Education)
Abstract BackgroundArtificial intelligence (AI) is set to shape the future of medical practice. The perspective and understanding of medical students are critical for guiding the development of educational curricula and training. ObjectiveThis study aims to assess and compare medical AI-related attitudes among medical students in general medicine and in one of the visually oriented fields (pathology), along with illuminating their anticipated role of AI in the rapidly evolving landscape of AI-enhanced health care. MethodsThis was a cross-sectional study that used a web-based survey composed of a closed-ended questionnaire. The survey addressed medical students at all educational levels across the 5 public medical schools, along with pathology residents in 4 residency programs in Jordan. ResultsA total of 394 respondents participated (328 medical students and 66 pathology residents). The majority of respondents (272/394, 69%) were already aware of AI and deep learning in medicine, mainly relying on websites for information on AI, while only 14% (56/394) were aware of AI through medical schools. There was a statistically significant difference in awareness among respondents who consider themselves tech experts compared with those who do not (PPP ConclusionsAI education should be introduced into medical school curricula to improve medical students’ understanding and attitudes. Students agreed that they need to learn about AI’s applications, potential hazards, and legal and ethical implications. This is the first study to analyze medical students’ views and awareness of AI in Jordan, as well as the first to include pathology residents’ perspectives. The findings are consistent with earlier research internationally. In comparison with prior research, these attitudes are similar in low-income and industrialized countries, highlighting the need for a global strategy to introduce AI instruction to medical students everywhere in this era of rapidly expanding technology.